GEOCHEMICAL EVALUATION OF THE LATE MAASTRICHTIAN SUBDUCTION-RELATED VOLCANISM IN THE SOUTHERN NEOTETHYS IN VAN AREA, AND A CORRELATION ACROSS THE TURKISH-IRANIAN BORDER - Çolakoğlu, Ali Rıza; Günay, Kurtulus; Göncüoğlu, M. Cemal; Oyan, Vural; Erdoğan, Kemal (Ofioliti, 2014)
The Yüksekova mélange to the NE of Van, close to the Turkish-Iranian border is part of the Berit-Elazig-Van ophiolitic belt. It structurally overlies the Bitlis-Pütürge metamorphic complex and includes the remnants of the southern Neotethys. The mélange complex comprises mantle rocks together with massive and pillowed lavas and dykes associated with late Maastrichtian micritic limestones and radiolarian cherts. The lavas are trachyandesite/basaltic, whereas the dykes are alkali basalt in composition. Both rock types were probably formed by low-degree partial melting of a mixed source including primitive mantle and depleted MOR mantle components, which were subsequently affected by subduction modification. The geochemical character constrains the formation of these basalts, yet the youngest ones dated in the Yüksekova mélange to an intra-oceanic subduction zone within the Neotethys at the end of Cretaceous. The new ages and the tectonic setting of the volcanic rocks are correlated with other oceanic assemblages (e.g., Khoy and Inner Zagros ophiolites in Iran) across the Turkish-Iranian border.